Assessment of tobacco heating product THP1.0. Part 2: Product design, operation and thermophysical characterisation - Eaton, Dan; Jakaj, Blerta; Forster, Mark; Nicol, James; Mavropoulou, Eleni; Scott, Kenneth; Liu, Chuan; McAdam, Kevin; Murphy, James; Proctor, Christopher J. (Regulatory toxicology and pharmacology, 2018)
A novel tobacco heating product, THP1.0, that heats tobacco below 245 °C is described. It was designed to eliminate tobacco combustion, while heating tobacco to release nicotine, tobacco volatiles and glycerol to form its aerosol. The stewardship assessment approach behind the THP 1.0 design was based on established toxicological principles. Thermophysical studies were conducted to examine the extent of tobacco thermal conversion during operation. Thermogravimetric analysis of the tobacco material revealed the major thermal behaviour in air and nitrogen up to 900 °C. This, combined with the heating temperature profiling of the heater and tobacco rod, verified that the tobacco was not subject to combustion. The levels of tobacco combustion markers (CO, CO2, NO and NOx) in the aerosol of THP1.0 were significantly lower than the levels if there were any significant pyrolysis or combustion. Quantification of other tobacco thermal decomposition and evaporative transfer markers showed that these levels were, on average, reduced by more than 90% in THP1.0 aerosol as compared with cigarette smoke. The physical integrity of the tobacco consumable rod showed no ashing. Taken together, these data establish that the aerosol generated by THP1.0 is produced mainly by evaporation and distillation, and not by combustion or pyrolysis. •Design and operation of THP1.0 tobacco heating product is described.•A 5-step thermophysical and thermochemical assessment is conducted on THP1.0.•THP1.0 forms its aerosol predominantly through evaporation and distillation.•Tobacco in THP1.0 is not subject to combustion.